Efectos de la aplicación de Ácidos Húmicos sobre la estructura de los suelos franco arenosos - Ortiz Rodríguez, Stalin Duverlin (2024)
This document deals with the effect of the application of Humic Acids on the structure of sandy loam soils. The objectives were to detail the physical properties of sandy loam soils and establish the benefits of the application of humic acids in sandy loam soils. The conclusions determined that a soil with a composition of 60% sand particles, 30% silt particles and 10% clay particles is classified as having a sandy loam texture. Humic acids induce chemical modifications in the sorption properties of the soil. Balance acidity and alkalinity levels in soils to adjust the proper pH. Humic acids prove to be an effective stimulant of root development. Organic humic amendments with a high content of Iron (Fe) assimilable by plants are recommended for the correction of basic, calcareous soils, low in organic matter and/or saline. These amendments provide plant-assimilable iron (Fe) in the form of ferrous sulfate, reduce iron (Fe) accumulation in the soil, prevent and alleviate iron chlorosis, mitigate soil erosion in sandy soils due to excessive rainfall, and have a cushioning effect on the soil. pH, promotes the formation of soil clay-humic complexes, improves cation exchange capacity (CEC), improves nutrient absorption, supplies a full spectrum of chelated micronutrients, chelates salts locked in the soil for assimilation and improves physical, chemical and biological properties. soil properties.